Cultivating resilience: Harnessing pyoverdine-producing Pseudomonas to contrast iron deficiency in cucumber plants - José María Lozano-González; Mónica Yorlady Alzate Zuluaga; Juan José Lucena; Sandra López-Rayo; Sonia Monterisi; Stefano Cesco; Youry Pii (Plant Stress)
Iron (Fe) deficiency in crops significantly reduces yield, impacting agricultural productivity worldwide. Synthetic Fe chelates are commonly applied as fertilizers to address this issue, but their synthetic nature and prolonged use poses environmental risks. Thus, inoculation of plant growth-promoting bacteria rises as an alternative to enhance Fe uptake in crops while minimizing reliance on synthetic chelates. This study aimed to examine the influence of Pseudomonas RMC4 inoculation and pyoverdine application on cucumber plants cultivated hydroponically under Fe deficiency conditions. Evaluations included the SPAD index, plant biomass, root morphology, Fe-chelate reductase activity, gene expression, and ionomic analysis. Following Fe deficiency, Pseudomonas RMC4 inoculation improved the SPAD index, increased dry weight, enhanced root development, and facilitated Fe acquisition mechanisms, thus, fostering the endogenous resilience of the plant to the limited Fe availability. This improvement was observed with bacterial inoculation or pyoverdine application alongside an insoluble Fe source (ferrihydrite). Overall, the results suggest the beneficial impact of Pseudomonas RMC4 inoculation in alleviating symptoms of Fe deficiency. Future studies will investigate bacterial application under field conditions to assess its potential in replacing synthetic Fe-chelates fertilizers in crop production in favor of more sustainable agriculture.